Diciesiete (Journal of Parents and Teachers, 2023)
Hector is a 17-year-old teenager. He frequently gets into trouble, which is why he is in a juvenile facility where he does not interact and runs away regularly. His attitude changes when they perform assisted therapy with dogs and he becomes fond of one of them called Sheep. Soon after, this dog is adopted, which is why he decides to run away to search for him with the support of his brother Ismael, who gives in and helps Héctor find Sheep. But first, they pick up their grandmother Cuca who lives in a nursing home and is about to die. The three together go in the caravan in search of answers to their personal and emotional conflicts. They go to the animal protection to locate the data of their dog; in addition, they pick up a dog with three legs. Then they go to the village of the grandmother to bury her in her niche next to her husband. This trip will help them get to know each other better, solve their problems and cultivate their brotherly love.
Keywords: educational film guide; teenagers; autism; family; juvenile center; therapy with animals; social inclusion; education and values